2015
DOI: 10.1080/00140139.2015.1005163
|View full text |Cite
|
Sign up to set email alerts
|

How does information congruence influence diagnosis performance?

Abstract: Diagnosis performance is critical for the safety of high-consequence industrial systems. It depends highly on the information provided, perceived, interpreted and integrated by operators. This article examines the influence of information congruence (congruent information vs. conflicting information vs. missing information) and its interaction with time pressure (high vs. low) on diagnosis performance on a simulated platform. The experimental results reveal that the participants confronted with conflicting inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Although there were only six discrepancies involving missing data, the two most common pilot responses were to either not detect the ID and continue COA, or to detect, investigate, and continue COA. These findings align with past research with differences in how pilots respond to various information conflicts (Chen & Li, 2015;Lipshitz & Strauss, 1997). Our finding that participants experiencing conflicting information most commonly investigated the information conflict and changed their COA is consistent with findings from Lipshitz and Strauss (1997) that individuals typically respond to conflicting information by conducting a cost/benefit analysis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although there were only six discrepancies involving missing data, the two most common pilot responses were to either not detect the ID and continue COA, or to detect, investigate, and continue COA. These findings align with past research with differences in how pilots respond to various information conflicts (Chen & Li, 2015;Lipshitz & Strauss, 1997). Our finding that participants experiencing conflicting information most commonly investigated the information conflict and changed their COA is consistent with findings from Lipshitz and Strauss (1997) that individuals typically respond to conflicting information by conducting a cost/benefit analysis.…”
Section: Discussionsupporting
confidence: 90%
“…Their findings suggest that individuals respond to incomplete/ ambiguous information by collecting additional information to reduce uncertainty, which are consistent with our findings that pilots in this situation who detected the incomplete/ambiguous information investigated the discrepancy (i.e., collected additional information) in all but one instance. Finally, consistent with Chen and Li's (2015) finding that performers respond very similarly to missing information and nondiscrepant information, presumably due to their assumption that the missing information is consistent with other sources, our findings indicate that when missing information is detected, pilots more frequently maintained the status quo and did not make a change to the COA.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Conflicting information has been shown to have deleterious effects on decision making including reduction in accuracy of decisions, longer decision times and less confidence that the decision was correct (Mosier, Sethi, McCauley, Khoo, & Orasanu, 2007;Chen and Li, 2015). In order to prepare pilots to perform effectively on the flight deck, pilots must be armed with the knowledge and skills to support them in assimilating the information, accurately assessing the situation, and making effective decisions.…”
Section: Methodsmentioning
confidence: 99%
“…The authors suggest that this may be due to pilots not realizing the risks associated with failing to perform a complete information search and recommend that pilots receive training focused on thorough information search and integration. Further, research has revealed that in a situation in which multiple sources of information are provided and can be in conflict, congruent, or a piece missing, performers' response to missing information was very similar to their response to congruent information, suggesting performers assumed the missing information was consistent with other sources (Chen & Li, 2015). Althought there is currently a heavy focus in aviation training on information search skills, referred to as cross-check; there is an opportunity to bolster this process by systematically training pilots how to determine which piece of information is more accurate using inductive conflict resolution skills.…”
Section: Techniques To Utilize In Response To Information Conflictsmentioning
confidence: 99%